413 Evaluation of the Validity of Virtual Reality Simulators in the Preclinical Training of Robotic Surgery. (28th February 2022) - Ali, T.
Abstract: Aim: Robotic surgeries are a form of minimally invasive procedures that decrease a patient's recovery time. They have been increasing in numbers and scope over the past decade. Yet, they do not have a standardized method of training nor accreditation. The significant learning curve associated with it makes it intimidating to approach despite its benefits. This structured review aims to evaluate the validity of virtual reality simulators–tools that help surgeons overcome the learning curve of robotic surgery in a pressure-free environment that ensures patients' safety. Virtual reality simulators have the potential of increasing the efficiency of robotic surgery as well as its uptake in general. Method: Literature electronic databases SCOPUS, MEDLINE and PubMed were searched and interrogated for studies related to the aim. Inclusion and exclusion criteria were then applied to filter out more relevant studies. Redundant studies were eliminated, and the s of the remaining studies were examined until relevant studies were selected. Results: Four prospective clinical trials were found and critically appraised by the Support Unit for Research Evidence (SURE) checklist. All studies comprised the evaluation of the face, content, and construct validity of a VR simulator. Conclusions: The studies confirmed face, content, and construct validation of specific VR simulators. Hence, they encourage the use of VR simulators in the development of training and accreditation programs for robotic surgery. However, more predictive, and concurrent validation studies must be performed in order to establish the legitimacy of VR simulators as valid tools of training and accreditation.